Operational Problems and Strategies of Restaurants in Northern Philippines - Dan Jayson S. Dingil; Diamonde Irishlee I. Laforteza; John Carl B. Pagulayan; Rizza D. Velasco; Karen Joy A. Catacutan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aimed to determine the operational problems and coping strategies of restaurants in Tuguegarao City, Philippines. The study employed quantitative research wherein fifty-five managers/owners were surveyed using a questionnaire. Results revealed that restaurant establishments faced operational problems such as pricing, employees and service reliability, food issues, location, and atmosphere/ambiance. Furthermore, restaurants use various strategies to cope with the operational problems they encounter. This suggests that encountering operational problems depends on the type of ownership of a restaurant. Moreover, the strategies to cope with operational problems encountered were used by restaurants, regardless of their type of ownership, length of operations, number of employees, and type of restaurant.